NILAI-NILAI PENDIDIKAN KARAKTER DALAM TRADISI APITAN MASYARAKAT SINGOCANDI KUDUS - Muchamad Munawir Asyari; Erik Aditia Ismaya; Muhammad Noor Ahsin (WASIS : Jurnal Ilmiah Pendidikan, 2021)
The purpose of this study is to analyze the reasons for the Singocandi Village community in implementing the Apitan tradition and to analyze the values of character education in the Apitan tradition of the Singocandi Village community.The research was conducted using a qualitative approach with descriptive types and field study methods. The research was conducted in Singocandi Village, Kota District, Kudus Regency. The data collection techniques are through observation, interviews, and document study. Primary data sources were obtained from the results of observations and interviews with the pundhen caretaker Mbah Buyut Punjol, village officials, and the traditional committee of Apitan Alms Earth, Singocandi Village. As for the secondary data sources, researchers were obtained from supporting documents. Testing the validity of the data used the technique and source triangulation techniques. In this study, technical triangulation was carried out by combining data received from observations, interviews, and documents. Meanwhile, source triangulation was carried out by combining interview data from various sources.The results showed that the reason Singocandi Village people still carry out the Apitan tradition is as a form of preserving the nation's cultural heritage and to respect the struggles of the ancestors of the Indonesian nation. In the Apitan tradition there are also character education values such as religious, honest, tolerance, discipline, creative, love for the country, social care, and caring for the environment that need to be instilled in the nation's future generations. Therefore, this tradition must be preserved and introduced to the future generations of the nation..